Advance and unmet need of health care for patients with rheumatoid arthritis in the German population–results from the German Rheumatoid Arthritis Population Survey (GRAPS) - Westhoff, G.; Schneider, M.; Raspe, H.; Zeidler, H.; Runge, C.; Volmer, T.; Zink, A. (Rheumatology (Oxford), 2009)
OBJECTIVES: To assess the quality of health care for RA patients in the general population of Germany. METHODS: A three-stage population survey was conducted to identify individuals with RA using a health care access panel (18-79 years; n = 70,112). A 20-item postal screening questionnaire of musculoskeletal symptoms and diagnoses was followed by a detailed questionnaire for those who indicated the possibility of having RA. Respondents who fulfilled the modified ACR decision tree, who reported an RA diagnosis, care by a rheumatologist or the use of DMARDs were asked to participate in a clinical examination by rheumatologists who diagnosed the participants and rated the adequacy of treatment. RESULTS: RA could not be ruled out in 1177 cases, of which 643 agreed to participate in the clinical examination, which was finally attended by 317 participants. Attendees did not differ with regard to any health or treatment measure from those who did not attend. Forty-one RA patients were detected. Of them, 93% had seen a rheumatologist at least once and 63% within the last 12 months. A total of 73% had received DMARD therapy at some time and 59% were currently receiving it. An unmet need for DMARDs was discovered in 29% of the RA attendees. It pertained almost exclusively to the seronegative cases of which 29% had a need to start and 17% to increase a DMARD therapy according to the opinion of the examining rheumatologist. CONCLUSION: Health care for RA patients has improved significantly since the last German RA survey in 1989. However, DMARD prescription still does not meet clinical recommendations, specifically in RF-negative patients. Since seronegative RA is a treatable disease, this group should not be overlooked.